An Enhanced Symmetrical Fault Detection during Power Swing/Angular Instability using Park’s Transformation - Jeevitha A; Devi S (Institute of Advanced Engineering and Science, 2016)
Power systems are subjected to a wide range of small or large disturbances during operating conditions. Power system disturbances such as line switching, generator disconnection and sudden removal of faults causes oscillations in an electrical machine rotor angles that can result in severe power swings. Depending on the protection controls, the system may remain stable or unstable and it may result in loss of synchronism. In recent years, distance relay finds difficulty between symmetrical fault and power swing which causes undesired tripping of the transmission line is the foremost reason for blackout. This paper proposes a new method Park’s Transformation and Fast Fourier Transform which are used to discriminate between the three phase fault and power swing and also to protect the backup zone of distance relay. This method is verified for normal and abnormal conditions with different load angles and different fault locations in IEEE 6-bus system are simulated in MATLAB/ Simulink. The Simulation results show the capability to avoid unwanted tripping decision of relay quickly and precisely.